A novel structurally identified epitope delivered by macrophage membrane-coated PLGA nanoparticles elicits protection against Pseudomonas aeruginosa - Chen Gao; Yin Chen; Xin Cheng; Yi Zhang; Yueyue Zhang; Ying Wang; Zhiyuan Cui; Yaling Liao; Ping Luo; Weihui Wu; Cheng Wang; Hao Zeng; et al. (Journal of Nanobiotechnology, 2022)
Abstract The increasing prevalence of antibiotic resistance by Pseudomonas aeruginosa (PA) raises an urgent need for an effective vaccine. The outer membrane proteins of PA, especially those that are upregulated during infection, are ideal vaccine targets. However, the strong hydrophobicity of these proteins hinders their application for this purpose. In this study, we selected eight outer membrane proteins from PA with the most significantly upregulated expression. Their extracellular loops were analyzed and screened by using sera from patients who had recovered from PA infection. As a result, a novel immunogenic epitope (Ep167-193) from PilY1 (PA4554) was found. Moreover, we constructed a macrophage membrane-coated PLGA (poly lactic-co-glycolic acid) nanoparticle vaccine carrying PilY1 Ep167-193 (PNPs@M-Ep167-193) that elicits a Th2 immune response and confers adequate protection in mice. Our data furnished the promising vaccine candidate PNPs@M-Ep167-193 while providing additional evidence for structure-based epitope identification and vaccine design. Graphical Abstract